2005
DOI: 10.1111/j.1540-8159.2005.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Variations in Optimal Programming of Cardiac Resynchronization Therapy Devices

Abstract: The optimal follow-up and long-term programming of cardiac resynchronization therapy (CRT) devices are uncertain. The aim of this study was to quantify the temporal variations in programming parameters to optimize the follow-up of these devices. Before, during, and at specified intervals over 9 months after implant, 40 recipients of CRT devices were studied. At each visit, the patients were tested with a fixed sequence of stimulation parameters during echocardiographic and electrocardiographic (ECG) recordings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 8 publications
3
56
1
Order By: Relevance
“…Whether and how AV intervals should regularly be evaluated and adjusted remains a matter of debate [7][8][9]. In various preliminary studies, optimization of the AV delay has been demonstrated to significantly increase hemodynamic response, New York Heart Association (NYHA) class, LVEF and B-type natriuretic peptide level in the short-time follow-up [10][11][12][13][14].…”
Section: Av Delay Optimization and Qrs Fusionmentioning
confidence: 99%
“…Whether and how AV intervals should regularly be evaluated and adjusted remains a matter of debate [7][8][9]. In various preliminary studies, optimization of the AV delay has been demonstrated to significantly increase hemodynamic response, New York Heart Association (NYHA) class, LVEF and B-type natriuretic peptide level in the short-time follow-up [10][11][12][13][14].…”
Section: Av Delay Optimization and Qrs Fusionmentioning
confidence: 99%
“…The guarantee to converge to the optimal AV delay and VV interval is the valuable benefit of using a sophisticated machine learning method, such as QL, in a CRT pacemaker. Since the AV delay and VV interval parameters are crucial for the success of the therapy [10][11][12][13]21], the guarantee to converge to the optimal AV delay and VV interval is an important advantage over other optimization methods that do not guarantee convergence to optimal values. Furthermore, this advantage should open the door to implementation of machine learning methods, such as QL, in implanted medical devices such as CRT pacemakers and defibrillators.…”
Section: Q Learning and Cardiac Resynchronization Therapymentioning
confidence: 99%
“…In addition the authors showed that changes from rest to exercise in LV dyssynchrony were correlated with changes in stroke volume and changes in mitral regurgitation. Odonnell et al [12] showed, in 43 CHF patients after CRT implantation in a follow-up study, that the optimal AV delay and VV interval found with echocardiography changed significantly over 9 months of follow-up period. G. Rocchi et al [13] showed recently that exercise stress Echo is superior to rest echo in predicting LV reverse remodelling and functional improvement after CRT.…”
Section: Introductionmentioning
confidence: 99%
“…If any ventricular remodeling has occurred, then the previously optimized values are likely to have changed. 58 The methodology of optimization is discussed later.…”
Section: Follow-up and Response To Therapymentioning
confidence: 99%